2018
DOI: 10.1002/cbic.201700691
|View full text |Cite
|
Sign up to set email alerts
|

The Un(f)told Story of General Anesthesia

Abstract: Inhalational anesthetics are routinely employed in clinical practice to accomplish general anesthesia. Concerns have recently emerged regarding the deleterious impact of these volatile agents on cognitive performance, immune functions, and tumor recurrence and metastasis. These agents have been shown to modify the gene-expression pattern as well as cell signaling in tumor cells, but the underlying molecular mechanisms remain a matter of conjecture. Regulatory/signaling proteins either of cytosolic or membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 203 publications
0
8
0
Order By: Relevance
“…The bisignate ECD bands at 515, 479 and 419 nm do not coincide with the maxima of the vibrational components in the absorption spectrum. The ECD bands of J aggregate are a result of the chiral exciton coupling, which is greatly different from that observed in H aggregate and come from the vibrionic components, which split individually . On the other hand, the sequence of ECD bands suggests the direction of packing arrangements for each type of aggregate .…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…The bisignate ECD bands at 515, 479 and 419 nm do not coincide with the maxima of the vibrational components in the absorption spectrum. The ECD bands of J aggregate are a result of the chiral exciton coupling, which is greatly different from that observed in H aggregate and come from the vibrionic components, which split individually . On the other hand, the sequence of ECD bands suggests the direction of packing arrangements for each type of aggregate .…”
Section: Resultsmentioning
confidence: 71%
“…Thus, the typical spectral changes that have been observed result from the arrangement of monomers into the aggregate structure, as well as from weak and reversible interactions like hydrogen bonds, van der Waals forces, π–π stacking and hydrophobic effects. Prior studies have highlighted the hydrogen bonding as a valid factor in the formation of carotenoid's H aggregate, especially in the case of ZXT and LUT . The hypothesis is affirmed by the fact that the formation of ZXT aggregates can be monitored by changing pH.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The analysis of the literature revealed that at the moment, fluoroorganic solvents of a new generation have appeared on an industrial scale in Russia; they have the advantages in a number of parameters in comparison to liquefied gases and supercritical fluids. Some fundamental parameters of fluoroorganic solvents and liquefied gases (from the technological point view) are presented in Table I [8][9][10][11][12][13]. As can be seen from the data in Table I, fluoroorganic solvents in many physical, chemical, environmental, and toxicological parameters do not differ very much from freons, but are inferior to carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%